2004
DOI: 10.1097/00004836-200402000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term Results of Endoscopic Treatment of Common Bile Duct Strictures in Chronic Calcifying Pancreatitis With Increasing Numbers of Stents

Abstract: Most chronic calcifying pancreatitis patients with common bile duct strictures respond to the increasing numbers of endoscopic stents, and remain stent free for medium term periods. Less patients (30%) does not benefit of biliary stenting, who are candidates for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 16 publications
0
52
0
3
Order By: Relevance
“…Morphological resolution of stenosis in long-term follow-up studies is obtained in no more than 10% of patients [205][206][207]. More aggressive endoscopic therapy, by placement of multiple plastic stents, can obtain stricture resolution in 44−90% of cases with a 13-48 months follow-up period after stent removal [208][209][210]. Although the role of self-expandable metal stents is well established for malignant obstruction, their use in benign strictures including chronic pancreatitis is less clear and controversial [211][212][213].…”
Section: E3: Is Endoscopic Therapy Indicated In Chronic Pancreatitismentioning
confidence: 99%
“…Morphological resolution of stenosis in long-term follow-up studies is obtained in no more than 10% of patients [205][206][207]. More aggressive endoscopic therapy, by placement of multiple plastic stents, can obtain stricture resolution in 44−90% of cases with a 13-48 months follow-up period after stent removal [208][209][210]. Although the role of self-expandable metal stents is well established for malignant obstruction, their use in benign strictures including chronic pancreatitis is less clear and controversial [211][212][213].…”
Section: E3: Is Endoscopic Therapy Indicated In Chronic Pancreatitismentioning
confidence: 99%
“…(40) Another study that focused on the insertion of multiple plastic biliary stents (7.5-to 10-Fr; 1-5 stents) increasingly in 29 patients at three-monthly intervals showed that after two years of stent placement, only 60% had stent-free recovery at a follow-up period of about one year. (41) …”
Section: Plastic Stentsmentioning
confidence: 99%
“…A Hungarian study evaluated 29 patients with common bile duct stricture due to chronic calcifying pancreatitis [75] . These patients received the maximum possible number of stents whenever the stents were changed (electively at 3 mo intervals or sooner if stent change was indicated).…”
Section: Chronic Pancreatitis Related Stricturesmentioning
confidence: 99%